2002
DOI: 10.1002/1521-4141(200204)32:4<1003::aid-immu1003>3.3.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Cruzipain, a major Trypanosoma cruzi antigen, conditions the host immune response in favor of parasite

Abstract: We recently demonstrated that humoral immune response to cruzipain, a major antigen of Trypanosoma cruzi parasite, is implicated in the pathogenesis of experimental Chagas' disease. In the present study, the spleen cell phenotype and the cytokine profile induced by cruzipain in immunized mice were analyzed. The results showed that cruzipain increases the number of spleen cells with large size and granularity. Splenocyte populations with CD19 + , Mac-1 + , Gr-1 + and CD11c + positive surface markers significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
50
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 9 publications
1
50
0
Order By: Relevance
“…After a comprehensive analysis of the kinetic of Ma subpopulations within infected myocardium, we found that M1 phenotype dominated only at short times postinfection (4 dpi), but then the M2 subset rapidly increased and predominated throughout the acute and chronic phase. The shift in M1/M2 rate observed may provide protection against overwhelming uncontrolled cardiac inflammation; however, the switch toward M2 profile can promote the parasite survival, which has evolved strategies to interfere with M1 activation and its microbicidal function (31,32). Considering that M1 Ma are responsible for resistance against T. cruzi through ROS and NO production and that the peak of parasitemia is reached at 18 dpi in the BALB/c infection model (24,33,34), we hypothesize that the sudden shift of M1 profile toward M2 subset at 7 dpi is too early, and, in consequence, the M1 influence is not enough to fight the parasite located into the myocardium.…”
Section: Discussionmentioning
confidence: 99%
“…After a comprehensive analysis of the kinetic of Ma subpopulations within infected myocardium, we found that M1 phenotype dominated only at short times postinfection (4 dpi), but then the M2 subset rapidly increased and predominated throughout the acute and chronic phase. The shift in M1/M2 rate observed may provide protection against overwhelming uncontrolled cardiac inflammation; however, the switch toward M2 profile can promote the parasite survival, which has evolved strategies to interfere with M1 activation and its microbicidal function (31,32). Considering that M1 Ma are responsible for resistance against T. cruzi through ROS and NO production and that the peak of parasitemia is reached at 18 dpi in the BALB/c infection model (24,33,34), we hypothesize that the sudden shift of M1 profile toward M2 subset at 7 dpi is too early, and, in consequence, the M1 influence is not enough to fight the parasite located into the myocardium.…”
Section: Discussionmentioning
confidence: 99%
“…Biological functions of MDSCs are mediated through a multitude of mechanisms and often have contrasting physiological implications. Although MDSCs were first characterized in tumorbearing mice and humans (50-52), they were also found to exist in healthy hosts and reported in other pathological conditions, including viral, bacterial, and parasitic infections (32,46,49,(53)(54)(55)(56). Not surprisingly, the implications for the MDSC-driven suppressive activities are dictated by the health or disease conditions in which they occur.…”
Section: Discussionmentioning
confidence: 99%
“…Papain family CPs such as papain itself (33), schistosome Ags (34), house dust mite Der p 1 (35,36), cruzipain from T. cruzi (37), and purified CPB2.8 from L. mexicana can induce Th2 responses (38). In several of these systems, including the L. mexicana CPB enzyme, this immune deviation required enzymatic activity and was not a passive Ag role.…”
Section: Discussionmentioning
confidence: 99%